Hybrid natural element - Boundary element method applied to solve electromagnetic scattering problem - Afonso, Marcio M.; Vasconcelos, Joao A.; Mesquita, Renato C.; Ramdane, Brahim; Marechal, Yves; Vollaire, Christian; Krahenbuhl, Laurent (2016 IEEE Conference on Electromagnetic Field Computation (CEFC), 2016)
In this paper the coupling of natural element method with the boundary element method (Hybrid NEM - BEM method) is proposed to solve the electromagnetic scattering problem. A dielectric cylinder is solved by the proposed approach and the results are compared with the analytical solution showing the usefulness and accuracy of the method.